1994
DOI: 10.1073/pnas.91.8.3358
|View full text |Cite
|
Sign up to set email alerts
|

A beta-lactone related to lactacystin induces neurite outgrowth in a neuroblastoma cell line and inhibits cell cycle progression in an osteosarcoma cell line.

Abstract: Lactacystin (structure 1 in Fig. 1) is a Streptomyces metabolite that inhibits cell proliferation and induces neurite outgrowth in the mouse neuroblastoma cell line Neuro 2A (1, 2). Cells induced to differentiate by treatment with lactacystin display a predominantly bipolar (two-neurite-bearing) morphology, particularly between 16 and 32 h after treatment, and become more multipolar (multiple-neurite-bearing) upon continued exposure, with increased branching of neurites. In contrast, serum deprivation or treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
135
1
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(148 citation statements)
references
References 24 publications
10
135
1
2
Order By: Relevance
“…Later studies on LTF, however, showed that bath application of the active form of lactacystin, clasto-lactacystin b-lactone, to sensory-motor neuron synapses resulted in enhanced LTF and an increase in neurite outgrowth in isolated sensory neuron (Zhao et al 2003). The increase in neurite elongation is consistent with results obtained in PC12 and Neuro2A cells in which lactacystin induces neurite outgrowth (Fenteany et al 1994). Both sets of results can be reconciled if one postulates that proteasome has different roles in different cellular compartments (Hegde 2004).…”
Section: Does the Proteasome Have Local Roles In Synaptic Plasticity?supporting
confidence: 79%
“…Later studies on LTF, however, showed that bath application of the active form of lactacystin, clasto-lactacystin b-lactone, to sensory-motor neuron synapses resulted in enhanced LTF and an increase in neurite outgrowth in isolated sensory neuron (Zhao et al 2003). The increase in neurite elongation is consistent with results obtained in PC12 and Neuro2A cells in which lactacystin induces neurite outgrowth (Fenteany et al 1994). Both sets of results can be reconciled if one postulates that proteasome has different roles in different cellular compartments (Hegde 2004).…”
Section: Does the Proteasome Have Local Roles In Synaptic Plasticity?supporting
confidence: 79%
“…Indeed, although some of the biochemical properties of the proteasome are well characterized (Orlowski, 1990;Orlowski et al, 1993), the physiologic functions of this proteinase complex have been di cult to study due to the lack of speci®c inhibitors. Recently, a novel streptomyces metabolite, lactacystin, discovered on the basis of its ability to induce neurite outgrowth in the murine neuroblastoma cell line Neuro-2A (Katagiri et al, 1995;Fenteany et al, 1994;Fenteany and Schreiber, 1996), has emerged as a highly speci®c, irreversible inhibitor of 26S proteasome chymotrypsin-like and trypsin-like activity, without a ecting lysosomal and nonlysosomal cysteine proteases, cathepsin or calpain (Fenteany et al, 1995). The inhibitory e ect of lactacystin on ubiquitin/ATP-dependent degradation of several proteins has been demonstrated both in mammalian cells (Blagosklonny et al, 1996;Bies and Wol , 1997;Oda et al, 1996;Mimnaugh et al, 1996;Lee and Goldberg, 1996; Je ers et al, 1997; Whitesell et al, 1997) and in yeast .…”
Section: Introductionmentioning
confidence: 99%
“…1) was discovered on the basis of its ability to inhibit cell growth and to induce neurite outgrowth in a murine neuroblastoma cell line, Neuro-2a (3). The cytostatic effects of lactacystin are not unique to Neuro-2a cells (4), and lactacystin has been found to inhibit cell cycle progression in both the G 0 /G 1 and G 2 /M phases of the cell cycle (4,5). Lactacystin treatment of Neuro-2a cells results in a predominantly bipolar morphology with two long processes emanating from opposite sides of the cell body, maximal between 16 and 32 h after the start of treatment (4).…”
Section: Lactacystin Inhibits Cell Cycle Progression In Different Celmentioning
confidence: 99%